Pengaruh Kompres Hangat Dan Kompres Air Dingin Terhadap Penurunan Nyeri Persalinan Kala I Fase Aktif Di Klinik Aras Srengseng Sawah Jakarta Selatan - Wahyuni, Dwi Reza; Azis, Aninditya; Mirawati, Mirawati (Bunda Edu-Midwifery Journal (BEMJ), 2024)
The research background: Handling pain during childbirth non-pharmacological methods such as, warm water compresses and cold compresses, breathing techniques, massage in the sacrum and cervical area, the use of the birth ball, and changes in position during labor and delivery companions. Warm compress techniques can maintain the components of the vascular system in a vasodilation state so that blood circulation to the pelvic muscles becomes homeostatic and can reduce anxiety and fear. The purpose of this study was to analyze the comparison of the effect of warm compresses with cold water compresses in reducing labor pain during the active phase I. The research method used was quasi-experimental with a pretest posttest control group design with a total sample of 80 maternity mothers during the I active phase of primigravida. The study was conducted from July to September 2023. Sampling used a non-probability sampling technique by consecutive sampling so that 40 respondents of the intervention group (warm compress) and 40 respondents of the control group (cold water compress) were obtained. The analysis of respondents' characteristics was tested using the Statistical Test of Shapiro Wilk, the difference in pain scale scores using the Wilcoxon test. comparison of the differences in the mean of the two groups using the Mann Whitney test. The results showed that the Z value -2.763, P value 0.006 < 0.05, there is a difference in the effect of warm compresses with cold water compresses in reducing labor pain during the active phase I. The conclusion of this study is that warm compresses are better than cold water compresses in reducing labor pain during the Active phase I.